Introduction: Gamevironments of the Past - A Broad Take on Games and History - Fewster, Derek; Grufstedt, Ylva (2016)
Notes on the workings of history in games, historical culture, game design,and putting together this special issue of gamevironments.
Keywords: gamevironments; Historical Consciousness; historical culture; History; Video Games